2018
DOI: 10.3386/w24277
|View full text |Cite
|
Sign up to set email alerts
|

Does E-Cigarette Advertising Encourage Adult Smokers to Quit?

Abstract: Only recently introduced into the U.S. market, e-cigarettes have been aggressively promoted, and use is increasing rapidly among both adults and youths. At the heart of the regulatory debate are fundamental questions regarding whether e-cigarettes will draw cigarette smokers away from a dangerous habit or lure new initiates into tobacco use. We provide some of the first causal evidence on whether e-cigarette advertising on television and in magazines (which comprise about 90% of total media spending on e-cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…We note that, while the studies apply different identification strategies, our findings are in line with Dave, Dench, Grossman, Kenkel, and Saffer (2018) who find no evidence that e‐cigarette magazine advertising influences quitting behavior among the US adult smokers. The authors do provide evidence that exposure to television e‐cigarette advertising may prompt some smokers to quit smoking.…”
Section: Discussionsupporting
confidence: 89%
“…We note that, while the studies apply different identification strategies, our findings are in line with Dave, Dench, Grossman, Kenkel, and Saffer (2018) who find no evidence that e‐cigarette magazine advertising influences quitting behavior among the US adult smokers. The authors do provide evidence that exposure to television e‐cigarette advertising may prompt some smokers to quit smoking.…”
Section: Discussionsupporting
confidence: 89%
“…Bypassing these sources of potential bias, we applied the method used in Dave et al . (2018) [19] to construct a measure of exposure to e‐cigarette advertisements for each person in the NCS, by matching advertisement placement data from Kantar to respondents in the NCS based on the programs that they watched and magazines that they read.…”
Section: Methodsmentioning
confidence: 99%
“…However, less is known about the impact of exposure to e‐cigarette advertisements on population‐level e‐cigarette use and conventional cigarette use and consumption among adults [18,19]. Existing studies have only assessed effects on the smoking cessation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have typically focused on a single population or age group, often with mixed results. For example, Dave and colleagues found that exposure to television e-cigarette advertisements was associated with cigarette smoking cessation amongst adults [24]. However, other studies have shown that e-cigarette advertising exposure is associated with increased urges to smoke cigarettes among cigarette smokers [22], as well as the use of other tobacco products including cigarettes, waterpipe tobacco, cigars, and polytobacco [25].…”
Section: Introductionmentioning
confidence: 99%